2012
DOI: 10.1063/1.3699040
|View full text |Cite
|
Sign up to set email alerts
|

Elastic cross sections for electron scattering from GeF4: Predominance of atomic-F in the high-energy collision dynamics

Abstract: We report absolute differential cross sections (DCSs) for elastic electron scattering from GeF4. The incident electron energy range was 3–200 eV, while the scattered electron angular range was typically 15°–150°. In addition, corresponding independent atom model (IAM) calculations, within the screened additivity rule (SCAR) formulation, were also performed. Those results, particularly for electron energies above about 10 eV, were found to be in good quantitative agreement with the present experimental data. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
55
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(67 citation statements)
references
References 39 publications
12
55
0
Order By: Relevance
“…As is evident from the level of agreement between the present experimental results and the IAM-SCAR calculation, the atomic-like effects are dominant in the scattering dynamics, even for the molecular structures. These features have been observed in several cases [45][46][47][48] at higher impact energies above 50 eV. But, it is worth noting that the atomic form factor of the S atom (atomic number: 16) plays an important role in the elastic scattering from OCS and CS 2 , more so than the other constituents of C (6) and O (8), over the impact energy from a few eV to 200 eV.…”
Section: Comparison Of the Dcss For Ocs Cs 2 And Atomic-smentioning
confidence: 96%
See 3 more Smart Citations
“…As is evident from the level of agreement between the present experimental results and the IAM-SCAR calculation, the atomic-like effects are dominant in the scattering dynamics, even for the molecular structures. These features have been observed in several cases [45][46][47][48] at higher impact energies above 50 eV. But, it is worth noting that the atomic form factor of the S atom (atomic number: 16) plays an important role in the elastic scattering from OCS and CS 2 , more so than the other constituents of C (6) and O (8), over the impact energy from a few eV to 200 eV.…”
Section: Comparison Of the Dcss For Ocs Cs 2 And Atomic-smentioning
confidence: 96%
“…As such, new measurements are compared with the existing experimental and theoretical data below 3 eV and above 100 eV. Also, following on from our series of studies on "atomic-like" effects which appear to prevail in high-energy electron scattering from molecules, [45][46][47][48] we further extend this study by comparing the elastic DCSs for OCS and CS 2 , where collisions with atomic sulphur appear to dominate the scattering dynamics. Further evidence lending support to this behavior is demonstrated by our IAM-SCAR results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our research program at Sophia University for such series of molecules, we have reported absolute differential cross sections (DCSs) for elastic electron scattering from CH n F 4-n (n = 0-4), 1, 2 XY 4 (X = C, Si, Ge; Y = H, F, Cl), [3][4][5][6] CX 3 Y (X = H, F; Y = H, F, Cl, Br, I), 7,8 C 3 H 8 and C 3 F 8 , 9 C 6 H 5 X (X = CH 3 , CF 3 ), 10 and CO 2 , OCS, and CS 2 . 11, 12 Those results have been compared with the corresponding elastic cross sections in Ne, Ar, Kr, and Xe (see, e.g., Ref.…”
Section: Introductionmentioning
confidence: 99%